Measure nicotine dependence by the fagerström test for nicotine dependence - WEBER,Caroline Francieli (2017)
ABSTRACT Objective To assess the level of nicotine dependence of smokers in a university dental clinic in southern Brazil using the Fagerström Test for Nicotine Dependence and identify those who would like to quit smoking. Methods A cross-sectional study was carried out with 93 Dental School patients, who underwent a face-to-face interview with four researchers. Data was analysed using descriptive statistics and the Chi-Square test with a significance level of 5%. Results The mean age of the smokers was 47.90 and most had had up to eight years of schooling, and had a family income of less than 1,000 Brazilian Reais. The degree of nicotine dependence was classified, by the mean, 4.45 ± 2.53 points (±SD). There was a significant correlation between nicotine dependence and the number of cigarettes smoked per day. Conclusion The 1% sodium hypochlorite solution caused least damage to the denture structure, not leading to decrease of the superficial microhardness.